Necessidade de treonina, metionina+cistina e lisina digestível para juvenis de tambaqui (colossoma macropomum) - Gonçalves Júnior, Lucas Pedro (2015)
Aiming to determine the nutritional needs of digestible threonine, methionine+cystine and lysine, for tambaqui (Colossoma macropomum). Three experiments were conducted in the Nutrition Laboratory and Production of Ornamental Species, Aquaculture Sector of the Federal Institute of Education, Science and Technology of the Espírito Santo Campus Alegre. All experiments were performed using the completely randomized design (CRD). The treatments of digestible amino acid (threonine = 0,70; 0,77; 0,84; 0,91; 0,98%; methionine+cystine = 0,66; 0,73; 0,80; 0,87; 0,94%; Lysine= 1,15; 1,45; 1,75; 2,05%). The basal diets were isonitrogenous (25% crude protein) and isocaloric (3200 Kcal.Kg-1 ). The experimental units consisted of eight tambaqui accommodated in boxes of usable volume of 40 L in water recirculation equipped for biological filtration and heater with thermostat. The productive performance was evaluated by weight gain (GP), feed conversion (CAA), protein efficiency rate (TEP), specific growth rate (TCE), hepatosomatic index (IHS) and the index of visceral fat (IGV). The results were submitted to variance of analysis and regression analysis. Quadratic effect was observed (P<0.05) levels of threonine in the specific growth rate and feed conversion. Threonine levels also influenced the protein efficiency ratio (P=0,057) and threonine efficiency rate (P=0,053)The methionine+cystine did not influence (P<0,05) hepatosomatic index, index of visceral fat and feed intake. The weight gain rate and efficiency of protein had (P<0,05) linear increase according to the methionine+cystine levels. The lysine levels did not affect (P<0,05) hepatossomatic index, visceral fat index, weight gain and feed intake. The total length and protein efficiency ratio showed a linear behavior (P<0,05) according to the lysine levels. Based on the results obtained it can be concluded that the levels of 0,98%, 0,94% and 2,05% threonine, methionine+cystine and lysine respectively meet the need for tambaqui.